Comparison of rural and urban contraceptive methods preferences among married women in Malaysia, 2018 - Nor Azah Samot @ Samat (Tanjung Malim, 2021)
Comparison of rural and urban contraceptive methods preferences among married women in Malaysia, 2018 by Nor Azah Samot @ Samat